The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/(sici)1520-6394(1997)5:2<97::aid-da6>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between objective and subjective sleep measures in depressed patients and healthy controls

Abstract: The purpose of this study was to correlate subjective sleep characteristics based on questionnaire response, and objective sleep EEG features based on polysomnography, in 52 patients with major depressive disorders (MDD) and 49 healthy controls. With the exception of the number of awakenings, subjective and objective sleep measures were strongly correlated in both groups. Patients and controls were able to accurately judge time in bed, total sleep time and sleep latency. However, sleep quality, depth, and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 16 publications
(21 reference statements)
6
103
3
Order By: Relevance
“…It should be kept in mind that, due to its largely subjective nature, sleep quality correlates with, but is not accurately defined by, sleep laboratory measurements. A previous study comparing subjective sleep characteristics assessed by questionnaire with objective measures obtained during polysomnography showed that, although individuals are able to satisfactorily judge time in bed, total sleep time and sleep latency, correlation between sleep quality and objective sleep characteristics is less strong (40). In summary, melatonin, as used in this study, has the potential to become a useful tool for the management of sleep problems in COPD patients.…”
Section: Discussionmentioning
confidence: 73%
“…It should be kept in mind that, due to its largely subjective nature, sleep quality correlates with, but is not accurately defined by, sleep laboratory measurements. A previous study comparing subjective sleep characteristics assessed by questionnaire with objective measures obtained during polysomnography showed that, although individuals are able to satisfactorily judge time in bed, total sleep time and sleep latency, correlation between sleep quality and objective sleep characteristics is less strong (40). In summary, melatonin, as used in this study, has the potential to become a useful tool for the management of sleep problems in COPD patients.…”
Section: Discussionmentioning
confidence: 73%
“…However, these impressions of disrupted sleep were not borne out by objective sleep measures in this study or in a previous study (Haney et al, 2003), suggesting that sleep disruption may not be a symptom of marijuana withdrawal. The differences between subjective and objective measures of sleep are not uncommon, particularly in individuals with mood disorders (Armitage et al, 1997). It may be that the mood symptoms of withdrawal skewed the subjective impression of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Equally constructive would be a head-to-head comparison of the app and subjective measures such as sleep diaries and questionnaires. Such instruments, while widely used in clinical practice despite conflicting reports of their reliability, [17][18][19][20] require active patient involvement and motivation, and are often abandoned as being burdensome and inconvenient. Sleep apps such as this one that passively collect comparable data may represent a potential substitute for sleep diaries, especially in patients with poor motivation to maintain useful logs of their sleep.…”
Section: (20%)mentioning
confidence: 99%